Pengaruh Content Marketing Dan Experiential Marketing Terhadap Keputusan Pembelian Konsumen (Studi Kasus Konsumen di Kecamatan Medan Tembung) - Fitriani, Rahma; Aisyah, Nur; Pribadi, Teddy (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This study aims to determine whether content marketing and experiential marketing have an influence on consumer purchasing decisions, a case study of consumers in Medan Tembung District. The data collection technique in this study used a questionnaire with a quantitative approach. The data analysis technique used is descriptive statistical analysis and multiple regression analysis. And hypothesis testing using SPSS 26. The results showed that partially content marketing has a significant positive effect on consumer purchasing decisions in consumer case studies in Medan Tembung District, and experiential marketing has little significant effect on consumer purchasing decisions for consumers in Medan Tembung District. Simultaneously content marketing and experiential marketing have a significant positive effect on consumer purchasing decisions, a case study of consumers in Medan Tembung sub-district.